2020
DOI: 10.1039/d0bm00183j
|View full text |Cite
|
Sign up to set email alerts
|

Size effect of human epidermal growth factor-conjugated polystyrene particles on cell proliferation

Abstract: Conjugation of growth factors to a carrier is a favorable method to improve their efficacy as therapeutic molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Based on these findings, Ketoconazole, Salicylic acid, Acetaminophen, Isoniazid, Piperazine, and Betahistine were not cytotoxic to A431 cells at the studied concentrations. Based on our previous work, EGF could induce Tyrosine 1173 (Y1173) phosphorylation of A431 cells [14]. Assessing the level of Y1173 phosphorylation following co-treatment with the drugs and EGF could be good evidence to investigate the drugs as potential EGFR-tyrosine kinase inhibitors.…”
Section: -3-results For the Experimental Sectionmentioning
confidence: 99%
“…Based on these findings, Ketoconazole, Salicylic acid, Acetaminophen, Isoniazid, Piperazine, and Betahistine were not cytotoxic to A431 cells at the studied concentrations. Based on our previous work, EGF could induce Tyrosine 1173 (Y1173) phosphorylation of A431 cells [14]. Assessing the level of Y1173 phosphorylation following co-treatment with the drugs and EGF could be good evidence to investigate the drugs as potential EGFR-tyrosine kinase inhibitors.…”
Section: -3-results For the Experimental Sectionmentioning
confidence: 99%
“…It has been demonstrated that GFs' immobilization leads to enhanced cell signalling and prolonged biological activity of the GFs. Immobilization of GF prevents its internalization upon binding to the receptor, resulting in continued cell signalling and enhanced biological activities compared to soluble GFs 68–70 …”
Section: Discussionmentioning
confidence: 99%
“…67 Furthermore, an increase in expression of KRT10 and Involucrin GFs. [68][69][70] Since the high-affinity receptor for KGF, FGFR2-IIIb/KGFR, is predominantly expressed by cells of epithelial origin, we wonder if KGF receptors are present on ASCs. Several studies showed a combination of KGF and some stimulating factors induced the differentiation of MSCs towards keratinocyte lineage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Limited by the micron scale, PLT@PDA‐DOX micromotors may be minimal to be uptaken by cells. [ 17 ] However, the nano‐sized PMP@PDA‐DOX are released when PLT@PDA‐DOX micromotors are activated by TME, which is easy to be uptake by cancer cells. Therefore, the red fluorescence signal characterized here inside cancer cells is speculated that mainly derived from the released PMP@PDA‐DOX in cancer cellular environment.…”
Section: Construction and Characterization Of Engineered Plt‐based Micro/nanomotorsmentioning
confidence: 99%